Effects of steam pelleting and extruding sorghum grain-soybean meal diets on phosphorus availability for swine - M Trotter; G Allee (Kansas Agricultural Experiment Station Research Reports, 1979)
Two feeding trials and three phosphorus balance studies were conducted to compare the effect of steam pelleting, extruding, and grinding on phosphorus availability. The results indicate that steam pelleting or extruding has little, if any, effect on the availability of phosphorus for finishing swine (100 to 220 lbs.).; Swine Day, Manhattan, KS, November 8, 1979
Keywords: Swine day; 1979; Kansas Agricultural Experiment Station contribution; no. 80-136-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 371; Swine; Steam pelleting; Sorghum; Phosphorus